2017
DOI: 10.1093/mnras/stx2202
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the IRX–β dust attenuation relation: exploring the physical origin of observed variations in galaxies

Abstract: The use of ultraviolet (UV) emission as a tracer of galaxy star-formation rate (SFR) is hampered by dust obscuration. The empirical relationship between UV slope, β, and the ratio between far-infrared and UV luminosity, IRX, is commonly employed to account for obscured UV emission. We present a simple model that explores the physical origin of variations in the IRX -β dust attenuation relation. A relative increase in FUV compared to NUV attenuation and an increasing stellar population age cause variations towa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
124
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(138 citation statements)
references
References 94 publications
14
124
0
Order By: Relevance
“…Both SMGs and cSFGs could be part of the same global population but observed in a different phase or intensity of the stellar mass assembly, with the SMGs reflecting the peak of the process and the cSFGs being a later stage. The cSFGs are consistent with an intermediate population between z>3 SMGs and z∼2 cQGs, caught in a phase where the star formation is winding down and a compact remnant is emerging, transitioning from the region above the MS of star-forming galaxies (Barro et al 2017) to the MS (Popping et al 2017a) and eventually below it. In fact, Elbaz et al (2017) recently showed that starburst galaxies exist both above and within the MS.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Both SMGs and cSFGs could be part of the same global population but observed in a different phase or intensity of the stellar mass assembly, with the SMGs reflecting the peak of the process and the cSFGs being a later stage. The cSFGs are consistent with an intermediate population between z>3 SMGs and z∼2 cQGs, caught in a phase where the star formation is winding down and a compact remnant is emerging, transitioning from the region above the MS of star-forming galaxies (Barro et al 2017) to the MS (Popping et al 2017a) and eventually below it. In fact, Elbaz et al (2017) recently showed that starburst galaxies exist both above and within the MS.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, simulations propose recent star formation in the outskirts and low optical depths in UV-bright regions as plausible explanations of the offset (Safarzadeh et al 2017;Narayanan et al 2018). Simple models placing a dust screen in front of a starburst have been studied to provide a detailed explanation of all the possible effects that might lead to a deviation in the IRX-β plane (Popping et al 2017b).…”
Section: Irx-β Planementioning
confidence: 99%
“…These properties ultimately depend on other physical properties of the galaxies, for example, their metallicity as shown in the case of SMC-like dust. We note that in the recent study by Popping et al (2017b), the low IRX values and red UV continuum slopes can also be explained by old and dust-poor stellar populations (see also Howell et al 2010). Observations are necessary in order to verify or disproof this solution for a given sample at high redshift.…”
Section: Analytical Models To Explain Irx−βin Typical Local Tomentioning
confidence: 75%
“…However, the IRX-β correlation is seen to break down as one moves from starburst galaxies to more "normal" SFGs (Kong et al 2004;Buat et al 2005;Hao et al 2011). This breakdown has been attributed to effects of evolved stellar populations, different star formation histories, variations in the dust/star geometry, and effects from the 2175Å feature (e.g., Boquien et al 2009;Grasha et al 2013;Popping et al 2017), all of which impact IRX and/or β values and introduce scatter.…”
Section: Variation Inmentioning
confidence: 99%